Explore tens of thousands of sets crafted by our community.
Differential Equations - Basics
35
Flashcards
0/35
\( \frac{dy}{dx} + y = 0 \)
\( y = Ce^{-x} \)
\( \frac{dy}{dx} + 7y = 0 \)
\( y = Ce^{-7x} \)
\( y'' - 16y = 0 \)
\( y = C_1e^{4x} + C_2e^{-4x} \)
\( y'' - y' - 6y = 0 \)
\( y = C_1e^{3x} + C_2e^{-2x} \)
\( y'' - 4y' + 5y = e^{2x} \)
\( y = C_1e^{2x}cos(x) + C_2e^{2x}sin(x) + \frac{e^{2x}}{4} \)
\( \frac{d^2y}{dx^2} - 2\frac{dy}{dx} + y = e^{x} \)
\( y = (C_1 + C_2x)e^{x} \)
\( y'' + y = tan(x) \)
This equation does not have a simple closed-form general solution.
\( \frac{dy}{dx} = 3x^2 \)
\( y = x^3 + C \)
\( \frac{dy}{dx} = cos(x) \)
\( y = sin(x) + C \)
\( \frac{d^2y}{dx^2} + 2\frac{dy}{dx} + y = x \)
\( y = -x + C_1e^{-x} + C_2xe^{-x} \)
\( y'' + y' - y = x^2 \)
\( y = C_1e^{x} + C_2e^{-x} + x^2 - 2x + 3 \)
\( \frac{d^2y}{dx^2} - 4\frac{dy}{dx} + 4y = 0 \)
\( y = (C_1x + C_2)e^{2x} \)
\( y' = e^{x} \)
\( y = e^{x} + C \)
\( y'' + 6y' + 9y = 0 \)
\( y = (C_1 + C_2x)e^{-3x} \)
\( y'' - 2y' + y = e^{x} \)
\( y = Ce^{x} - xe^{x} \)
\( \frac{d^2y}{dx^2} - 9y = 0 \)
\( y = C_1e^{3x} + C_2e^{-3x} \)
\( \frac{dy}{dx} + y = x \)
\( y = x - 1 + Ce^{-x} \)
\( y'' + 4y = 0 \)
\( y = C_1cos(2x) + C_2sin(2x) \)
\( y'' + y' - 2y = e^{-x} \)
\( y = C_1e^{2x} + C_2e^{-x} - \frac{1}{3}e^{-x} \)
\( y'' + 4y' + 4y = e^{-2x} \)
\( y = (C_1 + C_2x)e^{-2x} - \frac{1}{4}e^{-2x} \)
\( y' = y \)
\( y = Ce^{x} \)
\( y'' - 3y' + 2y = 0 \)
\( y = C_1e^{x} + C_2e^{2x} \)
\( \frac{d^2y}{dx^2} - y = cosh(x) \)
\( y = C_1e^{x} + C_2e^{-x} + \frac{1}{2}cosh(x) \)
\( y'' + y = 0 \)
\( y = C_1cos(x) + C_2sin(x) \)
\( y'' + 9y = 3sin(3x) \)
\( y = C_1cos(3x) + C_2sin(3x) + \frac{1}{18}xsin(3x) \)
\( y' - y = e^{2x} \)
\( y = Ce^{x} + \frac{1}{3}e^{2x} \)
\( \frac{d^2y}{dx^2} + 4\frac{dy}{dx} + 4y = x^2 \)
\( y = (C_1 + C_2x)e^{-2x} + x^2 - 4x + 8 \)
\( \frac{dy}{dx} = 5 \)
\( y = 5x + C \)
\( \frac{d^2y}{dx^2} = 6x \)
\( y = x^3 + C_1x + C_2 \)
\( y''' - y'' + y' - y = 0 \)
\( y = C_1 + C_2e^{x} + C_3e^{-x} \)
\( y''' - 6y'' + 9y' = x \)
\( y = C_1e^{3x} + C_2xe^{3x} + C_3x^2e^{3x} + \frac{1}{27}x^3 \)
\( \frac{dy}{dx} - 2y = 0 \)
\( y = Ce^{2x} \)
\( y' + 3y = 6 \)
\( y = 2 + Ce^{-3x} \)
\( y'' - y = 0 \)
\( y = C_1e^{x} + C_2e^{-x} \)
\( y' = y^2 \)
\( y = \frac{1}{C-x} \)
© Hypatia.Tech. 2024 All rights reserved.